Artificial methods of dentine caries induction: A hardness and morphological comparative study - Marquezan, Marcela; Correa, Fernanda Nahas P.; Sanabe, Mariane Emi [UNESP]; Rodrigues Filho, Leonardo Eloy; Hebling, Josimeri [UNESP]; Guedes-Pinto, Antonio Carlos; Mendes, Fausto Medeiros (Pergamon-Elsevier B.V. Ltd, 2009)
Objective: To assess the ability of two chemical and a microbiological methods to produce dentine caries lesions resembling naturally developed dentine caries lesions.Design: Forty sound second primary molars were divided into four experimental groups according to the method to produce artificial caries lesions: (1) sound (negative control); (2) acidified gel; (3) pH-cycling; and (4) microbiological, all for 14 days. Ten second primary molars presenting natural dentine caries lesions comprised the (5) positive control group. After the artificial caries induction, all samples were longitudinally sectioned and polished in order to obtain Knoop microhardness values from 10 to 500 mu m depth from the bottom of the cavities. Morphological analysis of the surfaces was carried out by SEM. Hardness data were compared among the five experimental groups using One-Way ANOVA and post hoc SNK's test.Results: The hardness values of chemically created caries-like lesions did not differ from that of natural caries lesions on shallower depths. The results indicated that chemical caries induction methods promote a superficial demineralization and that pH-cycling is more effective than acidified gel. The former, produced a thicker layer of demineralization, with similar hardness values than natural lesions. Despite the microbiological method provided an excessive softness of the primary dentine, this method presented morphology more comparable to natural lesions.Conclusions: pH-cycling is more appropriated to simulate a substrate that resembles affected caries dentine layer, after caries removal. The microbiological method seems more indicated to simulate a dentine caries lesion with an infected layer, previously to caries removal. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Artificial caries; Dentine caries; Microhardness; Scanning electron microscopy; pH-cycling; Microbiology; Gel